Genetic variant repressing ADH1A expression confers susceptibility to esophageal squamous-cell carcinoma. (1st May 2018) - Cui, Qionghua; Peng, Linna; Wei, Lixuan; Chang, Jiang; Tan, Wenle; Luo, Yingying; Huang, Xudong; Zhao, Yanjie; Li, Jun; Chu, Jiahui; Shao, Mingming; Zhang, Chao; et al.
Abstracts: Genome-wide association studies (GWAS) have discovered numerous genetic susceptibility loci including a cluster of alcohol dehydrogenase ( ADH ) gene family for esophageal squamous-cell carcinoma (ESCC). However, the underlying mechanism has not fully been elucidated. In this study, we integrated the GWAS data, gene-drinking interaction, expression quantitative trait locus (eQTL) analysis and biochemical experiments to clarify the specific mechanism of the polymorphisms in ADH loci. By imputation and eQTL analysis, we identified rs1154402C>G in intron 1 of ADH5 substantially associated with the expression levels of ADH1A . Association analysis showed that the rs1154402[G] allele was significantly associated with ESCC risk in drinkers (OR = 1.44, 95% CI = 1.20–1.73; P  = 7.74 × 10 −5 ) but not in nondrinkers (OR = 1.14, 95% CI = 0.93–1.37; P  = .220). Furthermore, the ADH5 variant showed a significant interaction with drinking and the genetic variant near ALDH2 encoding the enzyme oxidizing acetaldehyde, a carcinogenic product resulted from alcohol oxidation catalyzed by ADH s. We demonstrated for the first time that rs1154402C>G change might create a silencer, repressing ADH1A transcription via long-range interaction with ADH1A promoter. These results suggest that genetic variant in ADH5 might confer alcohol drinkers susceptible to ESCC by down-regulation of ADH1A, which weakens alcohol catabolism. Highlights: Genetic variant rs1154402 located in ADH5 represses the expression of ADH1A in a long range regulation. Attenuated expression of ADH1A due to the genetic variation rs1154402 may confer individuals susceptible to ESCC. Joint effect between rs1154402 in ADH5 and rs11066015 ALDH2 substantially increase the risk of ESCC.